The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1537-2995.2007.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and survey of the management of unexpected neonatal alloimmune thrombocytopenia

Abstract: BACKGROUND: Unexpected neonatal alloimmune thrombocytopenia (NAIT) may have devastating consequences and its management is challenging. To design future trials, evidence from the literature and existing best practice need review. STUDY DESIGN AND METHODS: This study was a cross‐sectional survey of neonatal units in Germany and Canada to determine management strategies of NAIT and a systematic search for randomized controlled trials (RCTs). RESULTS: Management of NAIT differs substantially between countries wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
13
0
4
Order By: Relevance
“…Preventing ICH by increasing platelet count above a certain threshold is therefore considered a neonatal emergency, and prompt correction by platelet transfusion should be done based on clinical suspicion without awaiting laboratory confirmation of the diagnosis 4. However, it is not clear what threshold should be used to trigger platelet transfusion 121,122. Previous reports also suggest that neonates with HPA-5b incompatibility may be at risk of bleeding at higher platelet counts compared with HPA-1 incompatibility 39.…”
Section: Managementmentioning
confidence: 99%
“…Preventing ICH by increasing platelet count above a certain threshold is therefore considered a neonatal emergency, and prompt correction by platelet transfusion should be done based on clinical suspicion without awaiting laboratory confirmation of the diagnosis 4. However, it is not clear what threshold should be used to trigger platelet transfusion 121,122. Previous reports also suggest that neonates with HPA-5b incompatibility may be at risk of bleeding at higher platelet counts compared with HPA-1 incompatibility 39.…”
Section: Managementmentioning
confidence: 99%
“…As with antenatal management, many important questions remain about the post‐natal management of NAIT. A recent systematic literature search failed to identify any randomised controlled trials or systematic reviews that compared different platelet thresholds for the transfusion of platelets for affected neonates and found that recommendations in the literature vary from a threshold of 30–100 × 10 9 /L 40 . This paper also surveyed clinicians and identified significant variation in transfusion practice.…”
Section: Post‐natal Managementmentioning
confidence: 99%
“…3 Unlike haemolytic disease in the newborn, AITP can also occur in the first pregnancy if there is parental incompatibility.…”
Section: Discussionmentioning
confidence: 97%